IDENTIFYING DETERMINANTS OF EMPLOYER BRANDING FOR FINAL-YEAR UNDERGRADUATE STUDENT IN ITB - Salsabila, Novira Aulia; Pritasari, Adita (Journal of Business and Management, 2018)
Abstract. Background: Challenges faced by companies today are the millennial generation that began to dominate the workplace and they tended to choose the others opportunities beside work in company after their graduated. In order for companies to be employer of choice for potential job seekers, the company needs to do employer branding. The aim of this study is to identify the determinants of employer branding in attracting ITB students as whole and also based on the faculty clusters to seek employment. Methods: This study using quantitative approach through questionnaires distributed to respondents by online media. In this study, researcher used Principle Component Analysis (PCA) in order to reducing the number of original variables and determining the right Employer Branding factors for final year Undergraduate Student in ITB. Results: After the reduction with PCA, there are seven factors formed for ITB as whole, six factors for Natural Sciences cluster, seven factors for Engineering cluster, and six factors for Social Sciences, Arts, and Humanities. Conclusion: The findings of this study can be useful for HRM professionals in the develop employer branding in order to attract potential employee from Institut Teknologi Bandung (ITB). This study also can help companies who targeted graduates from ITB to build desirable image that can fit with their value.Keywords: Employer Branding, Employer of choice, ITB, Millennials, PCAÃ‚Â